2022
DOI: 10.1080/13543784.2022.2049232
|View full text |Cite
|
Sign up to set email alerts
|

Progress and pitfalls in the use of immunotherapy for patients with triple negative breast cancer

Abstract: Introduction:Triple negative breast cancer (TNBC) is an area of high unmet medical need in terms of new effective treatment strategies. Although breast cancer is traditionally considered a 'cold' tumor type, TNBC is the most appropriate subtype for immunotherapeutic strategies; this is due to the high level of tumor infiltrating lymphocytes, PD-L1 expression, and tumor mutational burden compared to other breast cancer subtypes. Areas covered: This review examines the available evidence on the use of immunother… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 106 publications
1
27
0
1
Order By: Relevance
“…Moreover, all of the above findings might contribute to the notion of cancer immunoediting. Breast cancer has traditionally been considered less immunogenic except TNBC, which is regarded as the optimum subtype for immunotherapy because of high mutational frequency and increased concentrations of tumorinfiltrating lymphocytes (Agostinetto et al, 2022). Our study also showed that immune cells and related activities were lower in the high-risk group.…”
Section: )supporting
confidence: 56%
“…Moreover, all of the above findings might contribute to the notion of cancer immunoediting. Breast cancer has traditionally been considered less immunogenic except TNBC, which is regarded as the optimum subtype for immunotherapy because of high mutational frequency and increased concentrations of tumorinfiltrating lymphocytes (Agostinetto et al, 2022). Our study also showed that immune cells and related activities were lower in the high-risk group.…”
Section: )supporting
confidence: 56%
“…Subsequently, anti-PD1 in combination with neoadjuvant chemotherapy was approved for high-risk early-stage TNBC for curative intent. In spite of these successes, responses to check point inhibitors remain limited to a subset of TNBC patients [57][58][59] . As TILs frequency and PD1/PDL1 expression are not sufficient to predict response efforts have been concentrated on identifying additional predictive markers.…”
Section: Discussionmentioning
confidence: 99%
“…TLSs were studied predominantly in TNBC and HER2-BC molecular subtypes [ 40 , 41 , 42 , 43 ]. Most of the papers studied intratumor TLSs while stromal TLSs are not very well characterized regarding their topography and interrelation to peritumor adipose tissue.…”
Section: Discussionmentioning
confidence: 99%